PERANAN ULAMA DALAM MEMARTABATKAN TAMADUN ISLAM DI NUSANTARA: TUMPUAN TERHADAP ABDUL RAUF SINGKEL - Mohammad, Ali (Journal of Al-Tamaddun, 2009)
This article discusses the role of Muslim scholars in elevating Islamic Civilization in the Malay Archipelago. Compilation from contributions provided by them will be focused on a well-known figure, Sheikh Abdul Rauf Singkel. His role in elevating Islamic civilization can be viewed through several channels such as in the judicial field as Qadi Malik al-’Adil, active in the field of writing and he produced many works. He become spreader of newborn thinking and pioneer of Tarikat Syatariyah, active in the field of education. He was well-known with the title Teungku Syiah Kuala and established networks among scholars throughout Malay Archipelago. Sheikh Abdul Rauf Singkel role?s is huge and able to elevate the Islamic civilization in Malay Archipelago.